1989
DOI: 10.1002/ijc.2910440603
|View full text |Cite
|
Sign up to set email alerts
|

The copenhagen case‐control study of renal pelvis and ureter cancer: Role of analgesics

Abstract: Analgesic intake was investigated for 96 patients with cancer of the renal pelvis and ureter (including papillomas) and 294 hospital controls. In comparison with persons who never used analgesics, increased relative risks (RR) were seen for users of phenacetin-containing drugs after adjustment for smoking and high-risk occupational exposure (men: RR = 2.4; women: RR = 4.2). A significant relative risk for aspirin use among women was also observed. There was an indication of a dose-effect relationship for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Ross et al (20) described an increased risk of cancer of the renal pelvis and ureter of 2.3 (1.2-3.2) after an intake of aspirin but not of acetaminophen or phenacetin. Jensen et al (26) reported that aspirin users who had never taken phenacetin had increased relative risks but the estimates were highly unstable due to small numbers. Our results were of borderline significance statistically and apart from validity problems (vide infra) chance could explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Ross et al (20) described an increased risk of cancer of the renal pelvis and ureter of 2.3 (1.2-3.2) after an intake of aspirin but not of acetaminophen or phenacetin. Jensen et al (26) reported that aspirin users who had never taken phenacetin had increased relative risks but the estimates were highly unstable due to small numbers. Our results were of borderline significance statistically and apart from validity problems (vide infra) chance could explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These uncontrolled observations were later confirmed by a number of case-control studies conducted in diverse populations (McCredie et al, 1982;McLaughlin et al, 1985;Jensen et al, 1989). In 1987, the International Agency for Research on Cancer concluded that there was sufficient evidence to name phenacetin as a human carcinogen.…”
mentioning
confidence: 93%
“…All affected individuals in this kindred were heavy smokers but none was employed in a high risk occu pation. The mother died of colon adenocarcinoma, In a fol io wup study of this family, 2 sons with bladder cancer la te r had primary lung cancers, 16 Benton and Henderson presented the occupational h isto ries of 9 individuals w ith transitional cell carcinoma of th e bladder diagnosed before age 25 years. 17 One patient w as a 19-year-old repairm an with exposure to glues and solvents.…”
Section: Familial Transitional Cell Carcinoma Of the Bladdermentioning
confidence: 99%